A comparative study of the image of the devil in the logic of Attar Attar and the commentary of Abolfotuh Razi - Akbari, Mahtab (2021)
One of the most central themes in Sufi books and Persian commentaries is the subject of the devil and how he tells his story. In this research, in an analytical-descriptive manner, we have studied the image of the devil in the logic of Attar al-Tair and the interpretation of Ruz al-Jannan by Abul-Futuh Razi. We have analyzed the personal interpretations of Attar and Abolfotuh Razi from the story of Iblis and have shown the commonalities and differences between them in different parts of the story.